The journey of Tai-me - Momaday, N. Scott, frey50 (Albuquerque : University of New Mexico, 2009)
'Tai-Me' is a traditional medicine bundle used by the Kiowa in their Sun Dance. The bundle has been handed down from generation to generation, through the nineteenth century and into the twentieth. The author set out on his quest to learn and document the Kiowa heritage, stories, and folklore. This book gathers these stories.
Originally published: Santa Barbara : University of California, 1967. With new pref.
Keywords: Kiowa Indians; Folklore